Development of a mulberry core collection originated in China to enhance germplasm conservation - Yanfang,Zhang (2019)
Abstract China, origin of mulberry, has rich genetic resources usually. High expense, limited space and wavering environment of usually conservation in vivo poses dangerous situation for mulberry. The concept of core collection could takes priority for conservation of mulberry. In this study, 560 accessions were used with 40 morphological descriptors and stratified sampling strategies for a core collection. The core collection consisted of 28 accessions, accounting for 5% of the whole collection. The core collection included seven accessions belonging to Morus alba, one accession belonging to M. alba var. macrophylla, four accessions belonging to M. atropurprea, one accession belonging to M. nigra, three accessions belonging to M. australis, seven accessions belonging to M. multicaulis, two accessions belonging to M. wittorum and three accessions belonging to M. bombycis. The quality of core collection exceeded the evaluation criteria and could be a prioritized collection for high efficient and long-term conservation for mulberry.